2022
DOI: 10.1029/2021jd036140
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Snow in Controlling Halogen Chemistry and Boundary Layer Oxidation During Arctic Spring: A 1D Modeling Case Study

Abstract: Halogen chemistry has a large impact on tropospheric chemistry in the polar regions (e.g.,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 113 publications
2
3
0
Order By: Relevance
“…Piot and von Glasow (2009) used a box model to calculate the required fluxes of halogens to account for the observed effects on ozone in Alert, Canada in early spring, and estimated a Br 2 flux ranging from 5 × 10 7 to 1.5 × 10 9 molecules cm −2 s −1 . Other box and 1D modeling studies estimated maximum emissions of Br 2 of 2 -5 × 10 8 molecules cm −2 s −1 at Utqiagvik, Alaska in March (Ahmed et al, 2022;Wang & Pratt, 2017), within the same order of magnitude of those from previous observation-based estimates from the same site (Custard et al, 2017).…”
supporting
confidence: 68%
“…Piot and von Glasow (2009) used a box model to calculate the required fluxes of halogens to account for the observed effects on ozone in Alert, Canada in early spring, and estimated a Br 2 flux ranging from 5 × 10 7 to 1.5 × 10 9 molecules cm −2 s −1 . Other box and 1D modeling studies estimated maximum emissions of Br 2 of 2 -5 × 10 8 molecules cm −2 s −1 at Utqiagvik, Alaska in March (Ahmed et al, 2022;Wang & Pratt, 2017), within the same order of magnitude of those from previous observation-based estimates from the same site (Custard et al, 2017).…”
supporting
confidence: 68%
“…The study reported excess bromine in the springtime that could not be explained by known particle sources and ascribed it to partitioning of gaseous bromine produced from nonparticulate sources . In the current study, the measured gas-phase bromine could not be explained by particulate bromide alone (as explained below), and therefore, the enrichment of bromide in submicron aerosol particles prior to snowmelt is consistent with snowpack-produced Br 2 and BrCl, leading to atmospheric bromine recycling and the gas-particle partitioning of bromine-containing gases (e.g., HBr, HOBr, BrONO 2 ) …”
Section: Resultssupporting
confidence: 50%
“…75 In the current study, the measured gas-phase bromine could not be explained by particulate bromide alone (as explained below), and therefore, the enrichment of bromide in submicron aerosol particles prior to snowmelt is consistent with snowpack-produced Br 2 and BrCl, leading to atmospheric bromine recycling and the gas-particle partitioning of brominecontaining gases (e.g., HBr, HOBr, BrONO 2 ). 77 The slowdown of reactive bromine chemistry beginning in late April through the end of the study is evident in the measured particulate [Br − ] (Figure 3a). Prior to the onset of snowmelt (April 30−May 10), submicron particle bromide was elevated (0.3−2 ng m −3 ), compared to the levels after the snowmelt.…”
Section: Shutdown Of Reactive Bromine Chemistry In Latementioning
confidence: 93%
“…The extremely strong near-surface temperature inversion and low speed winds at the surface require a fine vertical grid to model the trapping of pollution from surface sources and also to model potential downwash from lofted sources such as power plants. Therefore, we used both 1-D chemistry-aerosol-transport models ,, with very fine grids and a special version of the Weather Research Forecast - Community Multiscale Air Quality (WRF-CMAQ) model tuned to Fairbanks and coupled with aerosol chemistry and WRF-Chem tuned to Arctic conditions . To model dispersion, we can couple meteorological fields from WRF with a Lagrangian model such as the FLEXible PARTicle dispersion model (FLEXPART) .…”
Section: Experimental/methodsmentioning
confidence: 99%